Pulsed monoclonal antibody treatment and autoimmune thyroid disease in multiple sclerosis. - Coles, A; Wing, M; Smith, S; Coraddu, F; Greer, S; Taylor, C; Weetman, A; Hale, G; Chatterjee, V; Waldmann, H; Compston, A (1999)
BACKGROUND: Multiple sclerosis results from T-cell-dependent inflammatory demyelination of the central nervous system. Our objective was long-term suppression of inflammation with short-term monoclonal antibody treatment. METHODS: We depleted 95% of circulating lymphocytes in 27 patients with multiple sclerosis by means of a 5-day pulse of the humanised anti-CD52 monoclonal antibody, Campath-1H. Clinical and haematological consequences of T-cell depletion, and in-vitro responses of patients' peripheral-blood mononuclear cells were analysed serially for 18 months after treatment. FINDINGS: Radiological and clinical markers of disease activity were significantly decreased for at least 18 months after treatment. However, a third of patients developed antibodies against the thyrotropin receptor and carbimazole-responsive autoimmune hyperthyroidism. The depleted peripheral lymphocyte pool was reconstituted with cells that had decreased mitogen-induced proliferation and interferon gamma secretion in vitro. INTERPRETATION: Campath-1H causes the immune response to change from the Th1 phenotype, suppressing multiple sclerosis disease activity, but permitting the generation of antibody-mediated thyroid autoimmunity.